KONSEKWENSI PENGRUSAKAN LINGKUNGAN HIDUP DI MASA PANDEMI DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 32 TAHUN 2009 - Ruhanda, Ruhanda (Ilmu Pemerintahan Universitas Langlangbuana, 2020)
The environment is an important factor for human sustainability. Seeing its strategic position, the government regulates the environment into a law that guarantees that no violation of the environment occurs. These articles which regulate the environment explicitly stipulate legal sanctions for violators who are threatened with a sentence both materially and formally with strict legal offenses. Covid 19 is suspected of being a genetically modified product which in the Law Number 32 of 2009 stipulates the threat of punishment if it is really a person or legal entity that violates the provision. In the 2009 UPPLH Law it does not explicitly mention criminal threats for acts that cause environmental pollution, these provisions are not discarded, but are clarified into acts that cause exceeding ambient air quality standards, water quality standards, seawater quality standards, or criteria the standard of environmental damage the legal implications are the same because environmental pollution and / or environmental damage is the same as the exceedance of the quality standard or the standard criteria for environmental damage.